2012
DOI: 10.1097/med.0b013e32835a1a1b
|View full text |Cite
|
Sign up to set email alerts
|

Management of congenital adrenal hyperplasia in childhood

Abstract: Purpose of review Congenital adrenal hyperplasia (CAH) can present management challenges to the pediatric clinician. Glucocorticoid replacement remains the cornerstone of treatment; however, there are new formulations and delivery mechanisms being studied. Clinicians continue to discuss the optimal treatment of patients from the prenatal stage, through infancy to adulthood. As well, the role of genetics in the clinical care of patients with CAH, and screening for complications, remain topics of discussion. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
1
10
1
Order By: Relevance
“…It was beyond the scope of our survey to look into the types of assays used. The use of salivary 17-OHP in comparison with serum levels has been reported to be more sensitive as it measures the bioactive free hormone and preferable as it is noninvasive and painless (11). In our survey, only one centre reported that they were in the process of setting up a service to do salivary 17-OHP for monitoring.…”
Section: Discussionmentioning
confidence: 66%
“…It was beyond the scope of our survey to look into the types of assays used. The use of salivary 17-OHP in comparison with serum levels has been reported to be more sensitive as it measures the bioactive free hormone and preferable as it is noninvasive and painless (11). In our survey, only one centre reported that they were in the process of setting up a service to do salivary 17-OHP for monitoring.…”
Section: Discussionmentioning
confidence: 66%
“…Since the core problem in classic CAH is cortisol shortage, the leading aim of therapy is its substitution as well as suppression of the hypothalamus (CRH) and pituitary gland (ACTH) with exogenous glucocorticoid in order to achieve inhibition of excess androgen production [7,8]. The first-choice drug is usually hydrocortisone, identical to natural cortisol, at a dose of 10-18 mg/m 2 of the body surface divided into three (four) doses per day [9,10]. However, in non-classic CAH forms, where levels of endogenous cortisol remain normal and values of other metabolites are only moderately elevated, the inclusion of suppressive treatment to bring the elevated CRH and ACTH levels down may generate adverse effects due to supra-physiological dosing of glucocorticoids.…”
Section: Congenital Adrenal Hyperplasia and Androgen Biosynthesismentioning
confidence: 99%
“…The possibility of using saliva to monitor 24 h cortisol profiles has also being explored. Salivary cortisol can be collected in a painless way and offers a measure of bioactive free hormone [96]. Dried blood spots have also been assessed as a means of 24 h steroid profiling using liquid chromatography tandem mass spectrometry [97].…”
Section: Monitoring Of Treatmentmentioning
confidence: 99%